Raman spectra of stoichiometric and hyperstoichiometric uranium dioxide - Manara, Dario; Renker, Burkhard (Journal of nuclear materials, 2003)
Raman spectra of stoichiometric and hyperstoichiometric uranium dioxide are presented, as measured on nuclear-grade UO 2 pellets treated under oxidising conditions to obtain different levels of hyperstoichiometry. The precipitation of higher oxides on the sample surface in contact with air, depending on the oxidation of the specimen, is observed. Modes revealing the formation on the surface of the compound U 3O 8, such as the line at 750 cm −1, are detected in specimens with bulk O/U ⩾ 2.09. Particular attention is given to the behaviour of the line observed for stoichiometric UO 2 at 1151 cm −1, attributed to the crystal electric field Γ 5→Γ 3 transition. According to the presented measurements, such line can be regarded as a fingerprint of the quasi-perfect fluorite structure. Results are discussed and compared with those of some previous publications results on the same subject.